Political expressionism : roots of social movements in Iran, the Middle East, and the world - Mohajer, Reza. (Lanham : Lexington Books, 2023)
"Political Expressionism represents a new era in the practice of Social Movements where the transition from print to digital mediums forever changed how people protest and communicate. This work applies a comparative historical approach looking at the trends of Social Movements in Iran, the Middle East, and the world"--
Dawn of the Political Expressionism Era -- Theoretical Foundation -- Roots of Social Movements in Iran -- Social Movements in the Middle East and the World -- Impact of ICTs on Social Movements -- Changes in ICT Trends -- Future of Social Movements.
Includes bibliographical references and index.
Keywords: Social movements -- Middle East; Social movements -- Iran; Social movements; Internet -- Political aspects -- Middle East; Internet -- Political aspects; Social media -- Political aspects -- Middle East; Social media -- Political aspects; Information technology -- Political aspects -- Middle East; Information technology -- Political aspects